Identification of urothelial cancer-associated 1 (UCA1) as a diagnostic biomarker of pre-eclampsia via regulating microRNA-16 and its downstream signaling pathway - Ye-Hong Xv; Wei Gao; Liao-Jv Wang (Archives of Medical Science)
Introduction In this study, we investigated the clinical value of using urothelial cancer-associated 1 (UCA1) and microRNA-16 (miR-16) as biomarkers for the diagnosis of pre-eclampsia (PE). Also, we compared the diagnostic values of miR-16, UCA1 and pregnancy-associated plasma protein-A (PAPP-A) in PE. Furthermore, we investigated the interaction between miR-16 and UCA1/PAPP-A.